The impact of a group based, remotely delivered weight loss intervention in women with polycystic ovary syndrome on ovulation, quality of life and body composition - Gorczyca, Anna M.; Steger, Felicia L.; Ptomey, Lauren T.; Montgomery, Robert N.; Mickelsen, Riley; Smith, Patricia; Donnelly, Joseph E.; Marsh, Courtney A. (Frontiers in Reproductive Health, 2022)
Background Obesity and visceral adiposity are associated with anovulation. The most common cause of anovulatory infertility in women of reproductive age is polycystic ovary syndrome (PCOS). We conducted this formative study to examine the effects of a remotely delivered, group-based lifestyle program for women with overweight/obesity and PCOS on ovulation, PCOS related quality of life (PCOSQ) and body composition. Methods Women with anovulatory infertility caused by PCOS (N = 12) were enrolled in a 6-month high-intensity weight management intervention. Participants were asked to attend 45 min., group behavioral lifestyle sessions, delivered remotely by a registered dietitian weekly across the 6-mo. study and comply with a reduced energy diet, increased physical activity (225 min/wk.), and self-monitoring of weight, physical activity and diet. Diets consisted of five portion-controlled meals (three shakes + two entrees), at least five servings of fruits/vegetables, and ad libitum non-caloric beverages daily. Wilcoxon signed-rank tests were used to assess changes in outcomes across the intervention. Results Twelve women received the weight loss intervention (mean age = 32.7 ± 4.2 yrs., BMI = 36.8 ± 4.5 kg/m2, 92% college educated), and 8 completed the intervention. Eight (67%) women reported ovulating during the intervention with an average time to ovulation of 57 ± 45 days. Women lost an average of 3.85 ± 5.94 kg (p = 0.02), decreased their BMI (−1.61 ± 1.09 kg/m2; p = 0.04), and waist circumference (−4.54 ± 3.03 cm; p = 0.04) over the 6-mo. intervention. Additionally, self-reported menstrual problems measured by PCOSQ significantly improved over the study (p = 0.03). Conclusion A multicomponent group-based, remotely delivered, lifestyle intervention delivered remotely is a feasible and potentially scalable option to achieve clinically relevant (>3%) weight loss in women with PCOS. Clinical trial registration www.clinicaltrials.gov, identifier: NCT03677362.